The impact of bodily experience on Paul's resurrection theology - Chang, Kai-Hsuan 1980- (London New York Oxford New Delhi Sydney T&T Clark, 2022)
"This volume argues that bodily experience contributed significantly to the development of Paul's ideas about resurrection, as seen in his extant letters"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Paul -- the Apostle, Saint; Bible -- Theology; Resurrection -- Biblical teaching; Human Body -- Religious aspects -- Christianity